K-ATP channels in dopamine substantia nigra neurons control bursting and novelty-induced exploration. - Schiemann, J; Schlaudraff, F; Klose, V; Bingmer, M; Seino, S; Magill, P; Zaghloul, K; Schneider, G; Liss, B; Roeper, J (2012)
Phasic activation of the dopamine (DA) midbrain system in response to unexpected reward or novelty is critical for adaptive behavioral strategies. This activation of DA midbrain neurons occurs via a synaptically triggered switch from low-frequency background spiking to transient high-frequency burst firing. We found that, in medial DA neurons of the substantia nigra (SN), activity of ATP-sensitive potassium (K-ATP) channels enabled NMDA-mediated bursting in vitro as well as spontaneous in vivo burst firing in anesthetized mice. Cell-selective silencing of K-ATP channel activity in medial SN DA neurons revealed that their K-ATP channel-gated burst firing was crucial for novelty-dependent exploratory behavior. We also detected a transcriptional upregulation of K-ATP channel and NMDA receptor subunits, as well as high in vivo burst firing, in surviving SN DA neurons from Parkinson's disease patients, suggesting that burst-gating K-ATP channel function in DA neurons affects phenotypes in both disease and health.